Sister-girl Talk: A Community-based Method for Group Interviewing and Analysis. Issue 2 (May 2022) - Mitchell, Charlayne F.; Ore, Ersula J.; Wutich, Amber; SturtzSreetharan, Cindi; Brewis, Alexandra; Davis, Olga I.
Leveraging ground-breaking work of Black feminist scholars alongside established techniques of focus group and community-based participatory research, we explain sister-girl talk as a novel method for collecting and analyzing group interview data with Black women. We outline the procedures for consultation, facilitation and preliminary analysis of the sister-girl talk method.